Penetration Testing System CERDAS With Brute Force Method - Merlang, Ronald; Siswanto, Apri (International Journal of Information Systems and Technology, 2025)
Security of access rights is an important aspect so that there is no misuse by individuals seeking profit. The national cybersecurity operations center and the state cyber code agency recorded 88 million cyber-attacks in 2020. In an effort to prevent attacks on CERDAS, the author conducted a study by raising the problem "Can the security system used by CERDAS prevent brute force attacks and how is the brute force attack process carried out". The purpose of this study was to test the login page security system used by CERDAS. The method used was NIST 800-115. The results of the study showed that the login page security system used by CERDAS had a gap against brute force attacks with a success rate of up to 100%. Based on the results of the study, CERDAS must improve the login page security system as an effort to avoid brute force attacks that aim to harm the system.